Height and bone age of Turkish children with goiter where this condition is endemic - Gedik, Yusuf; Teziç, Tahsin; Kazancıoğlu, Sinan; Kaya, Cemil (The Turkish Journal of Pediatrics, 1986)
The statural growth, bone age and serum T_4 and T_3 values of seventy-eight endemic goitrous children are evaluated. No retardation in height and bone age was found in the goitrous children and also there was no significant difference in the height age/bone age ratio between goitrous children with a low T_4 and those with a normal T_4 level.
Keywords: bone maturation; endemic goiter; height